NATURAL FEEDING OF SLUDGE WORMS (Tubifex sp.) WITH DIFFERENT FEEDING RATE ON GROWTH AND SURVIVAL RATE OF CTENOPOMA (Ctenopoma acutirostre) FISH SEEDS - muhammad atilah setiawan; muarif muarif; fia sri mumpuni (Universitas Djuanda, 2019)
The aim of this study was to determine the growth and survival rate of Ctenopoma fish seeds. This study used a completely randomized design with 3 treatments and 3 replications. The treatment in this study was a different feeding rate using natural feed of Tubifex sp namely A (8%), B (10%), and C (12%) ). The test fish used was Ctenopoma fish seeds with an initial length of 2.40 ± 0.10 cm and an initial weight of 0.32 ± 0.05 g. Fish seeds are cultivated for 28 days with feeding frequency twice a day. The results of research showed that the use of different feeding rate had an significantly different (P<0.05) on the specific growth rate and absolute length growth with the best results in the treatment C. The survival rate was not significantly different between treatments (P>0.05). Key Words: Ctenopoma, feeding rate, growth, survival rate